An investigation into the mechanism of protection by local passive immunization with monoclonal antibodies against Streptococcus mutans. - Ma, J K (1990)
Local oral passive immunization with Streptococcus mutans-specific monoclonal antibody (MAb) (Guy's 13) prevented recolonization by indigenous S. mutans in human volunteers who had first been treated with a conventional antibacterial agent (chlorhexidine). The F(ab')2 fragment of the MAb was as protective as the intact immunoglobulin G, but the Fab fragment of the molecule failed to prevent recolonization of S. mutans. In subjects receiving the MAb Fab fragment, S. mutans levels in dental plaque and saliva reappeared at a similar rate to that found in sham-immunized subjects who received either saline or a nonprotective MAb. In vitro, MAb had no bacteriostatic or bacteriocidal effect on S. mutans. However, S. mutans grown in the presence of either intact immunoglobulin G MAb or the F(ab')2 fragment formed very long chains, which resulted in clumping of the cells. S. mutans grown with either saline or the MAb Fab fragment formed significantly shorter chains, more characteristic of streptococcal growth in liquid media. The results suggest that the two binding sites of the MAb molecule may be an essential feature for preventing streptococcal colonization but that the ability to bind to phagocytes and activate complement which resides in the Fc fragment is not essential. Protection against colonization by S. mutans lasting up to 2 years was observed in immunized subjects, although MAb was applied over a period of only 3 weeks. Furthermore, functional MAb was detected up to 3 days following application of MAb to the teeth. The long-term protection could not be accounted for by a persistence of MAb on the tooth surface, and we have suggested that it may be due to a shift in the balance of the oral flora which discouraged recolonization by S. mutans. However, examination of the proportions of Streptococcus sanguis and veillonella species in the recolonization experiments failed to reveal a significant change in the proportions of either organism, which returned to approximately the preexperimental levels in both the immunized and control groups. These findings confirm the in vivo functional specificity of the MAb to S. mutans but are not consistent with the suggestion that S. sanguis or veillonella take over the niche vacated by S. mutans, unless the shift in the proportion of these organisms cannot be detected by the method used.